2009
DOI: 10.1037/a0016281
|View full text |Cite
|
Sign up to set email alerts
|

Testing possible mechanisms of deficient supra-second time estimation in adults with attention-deficit/hyperactivity disorder.

Abstract: Numerous studies indicate deficient time estimation in individuals with attention-deficit/hyperactivity disorder (ADHD). Several hypotheses have been raised to explain this deficit including delay aversion, vulnerability to nontemporal distractions, deficient working memory, as well as pure deficit in temporal processing. To test the different hypotheses, adults with or without ADHD performed a prospective time-estimation task under different conditions: with or without nontemporal distraction; and with or wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…Therefore, findings on the seconds scale support the presence of a faster internal clock in participants with ADHD. This is consistent with other evidence (e.g., Pollak, Kroyzer, Yakir, & Friedler, 2009), which suggests that alterations in timing can be separated from compromised working memory or delay aversion.…”
Section: Evidence Of a Faster Internal Clock In Participants With Adhdsupporting
confidence: 93%
“…Therefore, findings on the seconds scale support the presence of a faster internal clock in participants with ADHD. This is consistent with other evidence (e.g., Pollak, Kroyzer, Yakir, & Friedler, 2009), which suggests that alterations in timing can be separated from compromised working memory or delay aversion.…”
Section: Evidence Of a Faster Internal Clock In Participants With Adhdsupporting
confidence: 93%
“…In contrast, the expert panel considered also functions as important which did not play a central role in the majority of research on the clinical neuropsychology of adults with ADHD, such as time estimation. There is indeed evidence of altered time estimation and reproduction in individuals with ADHD (Barkley, Edwards, Laneri, Fletcher, & Metevia, 2001;Mette et al, 2015;Noreika, Falter, & Rubia, 2013;Pollak, Kroyzer, Yakir, & Friedler, 2009;Prevatt, Proctor, Baker, Garrett, & Yelland, 2011), nevertheless, measures of time estimation and reproduction have not been routinely used in the assessment of adults with ADHD. Taken together, our conclusion is twofold.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of that study compared three counting prevention methods: instructions not to count, the articulatory suppression method, and the administration of an interference task. Rattat and colleagues demonstrated that the instruction method most effectively prevented counting during time reproduction tasks [ 12 , 60 , 65 ]. Nevertheless, the possibility that the participants were not truthful with respect to counting during the time reproduction test cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%